Bridging the Cognitive Gap in Inclusive Physics Classes: Behavioral and Cognitive Responses of a Student with Intellectual Disabilities Characteristics to IT-Based Hybrid Flashcards - KharismaKharisma Rizqi Sofiya Nita Machabbah; Imam Sucahyo; Amira Hasnanuha Ulayya (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This study aims to develop and evaluate the feasibility of an information technology (IT)-based hybrid flashcard integrated with QR codes for teaching abstract physics concepts, specifically logic gates, in an inclusive classroom. Method: A convergent mixed-methods design was employed involving 14 regular students and one student with intellectual disabilities (Subject I). Quantitative data were collected through pre-tests, post-tests, and observation sheets, while qualitative data were obtained from classroom observations, interviews, and field notes. Quantitative data were analyzed descriptively, whereas qualitative data were analyzed through data condensation, data display, conclusion drawing, and source triangulation. Results: The developed media achieved a practicality score of 94% based on peer observations. Regular students demonstrated moderate conceptual improvement with an average N-Gain score of 0.55. Although Subject I showed lower post-test performance, qualitative findings indicated active participation and successful completion of learning activities with teacher guidance, suggesting that the media supported accessibility and engagement during learning. Novelty: Unlike previous studies that primarily investigated assistive technology in either regular or special education settings, this study provides preliminary evidence for implementing a physical-digital hybrid learning medium within a heterogeneous inclusive classroom, where one instructional medium simultaneously supports regular students and a student with intellectual disabilities despite limited availability of Special Education Teachers (SETs).